Praktik Nikah Mut’ah Pra dan Pasca Revolusi Islam Iran - Hadi, Farid Nurul; Sulfinadia, Hamda; Efrinaldi, Efrinaldi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
The practice of temporary marriage (nikah mut'ah) in Iran has a long and complex history, closely related to the interpretation of Islamic law and social dynamics within Iranian society. This is marked by the complex unfolding of the Islamic revolution in Iran. Therefore, this study aims to understand the journey of family law in Iran and its development related to the phenomenon of nikah mut'ah practice before and after the Islamic revolution. This research is a literature study. The results of this study show that before the Islamic Revolution in 1979, this practice was less common and often viewed with diverse perspectives by society. However, after the Islamic Revolution, with the new government based on Sharia, the practice of nikah mut'ah gained legal legitimacy and broader support as part of the interpretation of Shia law. Nevertheless, this practice remains controversial and sparks debate among scholars and the wider community regarding its ethical and social aspects.